Avaliação das estratégias de ensino atencionais: a prática pedagógica para o aluno com Transtorno Déficit de Atenção/Hiperatividade - TDAH - Alencar, Maria de Jesus Queiroz de (2006)
This work intends to evaluate the pedagogica teachers of students with ADDH (Attention Deficit Disorder Hiperactivity): presence of attentional teaching strategies. It was also intended to investigate the concept of ADDH, verify the main difficulties related to apprenticeship and identify the attentional teaching strategies developed. This disorder is on of the most frequent disorders in school age children, with an incidence between 3 and 6% of these children. Inattention, impulsiviness, forgetfulness, excessive motor activity in levels which are not adequate to the stage of development of the individual are considered primary symptoms of this disorder. These characteristics interfere specially in the school perfomance of the student, occuring in an academic performance clearly inferior to his/her capabilities, although he/she is as intelligent as any other child. Cognitive mechanisms – attention, memory, motivation – directly involved in ADD are modified implying in more difficulty for the student in developing and using learning strategies. This requires support teaching strategies that must be used by the teacher. Specifically in students with this disorder in which the attention deficit is observed, strategies that help the maintenance of this struture are essential for apprenticeship, considering this, a qualitative study was conducted with 3 subjects. First through fourt grade teachers of both private and public schools of Fortaleza. The intention was to collect from these subjects the teaching strategies (of attention) developed in the clssroom at first, systematic observation in the clssroom was conducted, afterwards there were semi structureds interviews with these subjects and informers – principals and apprenticeship corenselors. The results indicatid a superficial conceptual framework in relation to the concept of ADD from the subjets as will as from the informers. In consonance with the informers the teachers revealed elementary knowledge of the main interferences of this disorders in apprenticeship. The pedagogical inadequation to the peculiarities related to the apprenticeship of students with ADD was apparent. The information collected revealed that the teachers developed attention teachig strategies in an emperie way, based on trials and mistakes without a consistent theor–tical support.